2012
DOI: 10.1016/j.rmed.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human antibacterial peptide LL-37 in the pathogenesis of chronic obstructive pulmonary disease

Abstract: This study suggested that LL-37 may play important role in the pathogenesis of COPD and may be a possible novel therapeutic target in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…LL-37 and small airway remodeling C Sun et al 16HBE cells with different concentrations of CSE and found that CSE leads to a significant elevation of LL-37 in 16HBE cells, which is in accordance with our previous study that CSE enhanced LL-37 expression in human bronchial epithelial cells and alveolar epithelial cells. 20 Similarly, a-defensin was also reported to be induced by CSE in human alveolar epithelial cells and gingival epithelial cells, 32,33 indicating a potential effect of cigarette smoke on AMP's expression in epithelial cells.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…LL-37 and small airway remodeling C Sun et al 16HBE cells with different concentrations of CSE and found that CSE leads to a significant elevation of LL-37 in 16HBE cells, which is in accordance with our previous study that CSE enhanced LL-37 expression in human bronchial epithelial cells and alveolar epithelial cells. 20 Similarly, a-defensin was also reported to be induced by CSE in human alveolar epithelial cells and gingival epithelial cells, 32,33 indicating a potential effect of cigarette smoke on AMP's expression in epithelial cells.…”
Section: Discussionmentioning
confidence: 95%
“…30 Furthermore, increasing body of literature demonstrates that the remodeling processes of the small airways may attribute to excessive production of growth factors by airway epithelium. 4,31 Based on the previous findings that LL-37 levels in small airway epithelium of COPD patients were significantly higher than control subjects, 20 we began to investigate whether epithelial production of LL-37 was involved in small airway remodeling in COPD. In line with our previous findings, a marked upregulation of LL-37 expression was observed in small airways from COPD smokers compared with nonsmokers and smokers without COPD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations